Analysis of The Configuration and Parameters of Transceiver Systems For The Purposes of Unmanned Aerial Vehicle - Adam OLESINSKI; Zbigniew PIOTROWSKI (Communications of International Proceedings, 2021)
The article presents the current threats related to Unmaned Aerial Vehicles (UAVs) and highlights the weakness of radio jamming technologies. Attention was paid to the possibility of designing or redesigning consumer market drones to other, insensitive to jammers, frequencies. The balance of the link between the operator and the UAV was presented, taking into account the median noise power for different frequencies and distances, in order to estimate the transmitter power for different frequencies of the drone. Radio solution for custom frequency drone was proposed.
Keywords: unmanned aerial vehicle (UAV); drone; radio link balance; radio jamming